2008
DOI: 10.1007/s10800-008-9491-9
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence of oxygen evolution from Li1+x (Ni1/3Mn1/3Co1/3)1−x O2 at high potentials

Abstract: Li 1+x (Ni 1/3 Mn 1/3 Co 1/3 ) 1-x O 2 (NMC) oxides are among the most promising positive electrode materials for future lithium-ion batteries. A voltage ''plateau'' was observed on the first galvanostatic charging curve of NMC in the extended voltage region positive to 4.5 V vs. Li/Li + for compounds with x [ 0 (overlithiated compounds). Differences were observed in the cycling stability of the overlithiated and stoichiometric (x = 0) NMC oxides in this potential region. A differential plot of the charge vs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
66
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 14 publications
10
66
0
1
Order By: Relevance
“…SLS-00 and SLS-10 samples were cycled galvanostatically in standard coinlike test cells and their cycling stability was as reported earlier. 7 It can be seen from Fig. 2 that, as expected, the overlithiated NMC (SLS-10) has better charge retention compared to the stoichiometric NMC (SLS-00) after few cycles.…”
Section: Resultssupporting
confidence: 69%
“…SLS-00 and SLS-10 samples were cycled galvanostatically in standard coinlike test cells and their cycling stability was as reported earlier. 7 It can be seen from Fig. 2 that, as expected, the overlithiated NMC (SLS-10) has better charge retention compared to the stoichiometric NMC (SLS-00) after few cycles.…”
Section: Resultssupporting
confidence: 69%
“…For Li-rich NMC materials (Li 1+x (Ni,Mn,Co) 1-x O 2 ) the total amount of released lattice oxygen is comparably large in the first cycle. [32][33][34][35][36] For this material class Strehle et al 36 found a ratio of O 2 /CO 2 close to 1/1 in contrast to ∼1/20 for the NMC materials (s . Table II), which based on Eq.…”
Section: Discussionmentioning
confidence: 92%
“…19,20 At first sight, this seemed consistent with the mass spectrometrically detected O 2 and CO 2 evolution starting during the activation plateau, which was interpreted to indicate the release of Li 2 O from the bulk of the material during activation and accompanying structural changes within the bulk material. 15,17,18,23,24 However, the exact quantification of the released oxygen by Strehle et al and Luo et al revealed that the amount of released oxygen is an order of magnitude too low to be consistent with the assumed electrochemical oxygen release 25,26 and also that the O 2 evolution does not start until right after the activation plateau (only <10 μmol O2 /g AM during the plateau, but >100 μmol O2 /g AM following thereafter; shown by Strehle et al). 25 Both observations suggested that the observed oxygen release cannot be ascribed to a loss of oxygen from the bulk of the material, but that the oxygen is only being released from the near-surface Thus, more recent studies propose that bulk and surface of these overlithiated materials show distinctly different properties, rationalized by a bulk-shell model.…”
mentioning
confidence: 97%
“…Initially, it was thought that during the first cycle activation plateau at ≈4.5 V vs. Li + /Li an electrochemical activation of redox inactive Li 2 MnO 3 would take place, leading to a release of bulk lattice oxygen and to an electrochemically active LiMnO 2 phase which could charge compensate Li extraction to capacities >200 mAh/g. [15][16][17][18] This oxygen release was ascribed to cause strong structural changes within the bulk material, ultimately leading to a layered-to-spinel transformation of the particles. This transformation of the bulk material was believed to lead to the HE-NCM specific phenomena such as voltage fading and hysteresis.…”
mentioning
confidence: 99%